Male partner attendance of skilled antenatal care in peri-urban Gulu district, Northern Uganda - Tweheyo, Raymond; Konde-Lule, Joseph; Tumwesigye, Nazarius M.; Sekandi, Juliet N. (BMC pregnancy and childbirth, 2010)
Male partner attendance of skilled Antenatal Care (ANC) is beneficial to improving maternal outcomes. This study investigated the level, perceived benefits and factors associated with male partner attendance of skilled ANC in a peri-urban community recovering from two decades of civil conflict. This cross-sectional survey used multi-stage sampling in 12 villages of Omoro county to select 331 married male respondents aged 18 years or more, whose female spouses had childbirth within 24 months prior to the survey. A structured questionnaire elicited responses about male partner attendance of ANC during pregnancy at a public health facility as the main outcome variable. Analysis used Generalized Linear Model (GLM) in Stata version 10.0 to obtain Prevalence Risk Ratios (PRR) for association between the binary outcome and independent factors. All factors significant at p < 0.15 and potential confounders were included in the multivariable model. Overall, 65.4% (95%CI; 60.3, 70.5) male partners attended at least one skilled ANC visit. Mean age was 31.9 years [SD 8.2]. Perceived benefits of attending ANC were: HIV screening (74.5%), monitoring foetal growth (34%) and identifying complications during pregnancy (18.9%). Factors independently associated with higher ANC attendance were: knowledge of 3 or more ANC services (adj.PRR 2.77; 95%CI 2.24, 3.42), obtaining health information from facility health workers (adj.PRR 1.14; 95%CI 1.01, 1.29) and if spouse had skilled attendance at last childbirth (adj.PRR 1.31; 95%CI 1.04-1.64). However, factors for low attendance were: male partners intending their spouse to carry another pregnancy (adj.PRR 0.83; 95%CI 0.71, 0.97) and living more than 5 Km from a health facility (adj.PRR 0.83, 95%CI 0.70, 0.98). Men who were knowledgeable of ANC services, obtained health information from a health worker and whose spouses utilised skilled delivery at last pregnancy were more likely to accompany their spouses at ANC, unlike those who wanted to have more children and lived more than 5 km from the health facility. These findings suggest that empowering male partners with knowledge about ANC services may increase their ANC participation and in turn increase skilled delivery. This strategy may improve maternal health care in post conflict and resource-limited settings.
Keywords: Male Partner; Maternal Mortality Ratio; Maternal Health Care; Male Involvement; Safe Motherhood